JEM 2021
DOI: 10.17576/jem-2021-5502-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity Effect of Central Bank Independence on Asset Prices: Evidence from Selected Developing Countries

Abstract: The study analyzes the response to financial asset prices and economic activity concerning central bank independence (CBI) shocks in selected developing countries. Financial asset prices were divided into the exchange rate, bond yield, and stock price, while the analysis was contingent on a panel Vector Autoregressive estimation. Furthermore, this study identifies heterogeneity across the countries in its sample through poolability tests. This is achieved through a mean-group estimation to the panel Vector Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Consequently, the investors will believe that national economic policy will be stable and consistent (Pastor & Maxfield, 1999). This evidence appears to support the work of Förch and Sunde (2012) and Anwar (2021a), who found that CBI changes are related to higher stock traded. The different effect of the CBI on stock traded in both groups could be because there is a different market capitalization in both groups.…”
Section: Empirical Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…Consequently, the investors will believe that national economic policy will be stable and consistent (Pastor & Maxfield, 1999). This evidence appears to support the work of Förch and Sunde (2012) and Anwar (2021a), who found that CBI changes are related to higher stock traded. The different effect of the CBI on stock traded in both groups could be because there is a different market capitalization in both groups.…”
Section: Empirical Findingssupporting
confidence: 88%
“…Consequently, the investors will believe that national economic policy will be stable and consistent (Pastor & Maxfield, 1999). This evidence appears to support the work of Förch and Sunde (2012) and Anwar (2021a), who found that CBI changes are related to higher stock price returns over 1 month. Nonetheless, stock price does not respond significantly over a period of 12 months after the CBI shock.…”
Section: Empirical Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…Globalization has increased capital mobility and international trade, affecting in larger CA deficits for many nations [2,3,4] The 2008-09 global financial crisis caused the world economic growth to drop to -1.6% in 2009 from 4.3% in 2007. This showdown negatively impacted international financial markets, workforce, industrial production, and consumption [5]- [7]. The economic recession could have resulted from several important indicators, such as rising world oil prices, which pushed up food prices, resulting in global inflation [8].…”
Section: Introductionmentioning
confidence: 99%